(untitled) (Global Journal of Science Frontier Research, 2018)
The hexane extracts of Jasminum sambac L. leaves damaged by jasmine leaf webworm, Nausinoe geometralis (Guenee) and also healthy jasmine laeves were subjected to Gas Chromatography-Mass spectrometry (GC-MS) to determine the saturated hydrocarbons. The results revealed that both the healthy and damaged leaves had hydrocarbon compounds numbering 21 and 27 respectively. The variation in the hydrocarbon profile of healthy and damaged leaves might be related to the quality of semiochemicals these plants emit, which is important for the attraction of natural enemies in jasmine ecosystem so as to reduce further infestation by budworm. In the healthy jasmine leaves, the hydrocarbons, hentriacontane and tetracosane were detected at 25.89 mins exhibiting the largest peak area of 24610830 mm 2 octacosane, tetracosane, eicosane, nonacosane and heptacosane followed the order and emitted in enormous quantities.